Pengaruh Literasi Keuangan dan Sikap Keuangan terhadap Perilaku Keuangan pada Mahasiswa - Hanifa Zahwa Virani; Fenty Fauziah; Sri Wahyuni Jamal (Yayasan Literasi Sains Indonesia, 2025)
This study aims to evaluate the influence of financial literacy and financial attitude on the financial behavior of students in the Management Study Program at Universitas Muhammadiyah Kalimantan Timur. The results show that financial literacy and financial attitude have a positive and significant effect on students' financial behavior, both partially and simultaneously. Financial literacy, which includes aspects of knowledge, skills, and confidence in managing money, is assumed to be closely related to wise financial decision-making. On the other hand, financial attitude, which reflects an individual’s views and judgments toward financial matters, also contributes to the formation of daily financial habits. This research employs a quantitative approach with an associative method. Data were obtained from 100 respondents selected using purposive sampling and analyzed using multiple linear regression to determine the influence between variables. These findings emphasize the importance of integrating financial education and fostering positive attitudes in supporting healthy personal financial management among students. Therefore, educational institutions are expected to play an active role in developing practical financial literacy programs and encouraging the formation of responsible financial behavior. These efforts serve as a crucial foundation for equipping students with the necessary skills and mindset to navigate future financial challenges effectively and independently.